Research on Neutral Point Drifting Technology Based on the Same Harmonic Distribution of Line Voltage - 徐振; 罗仁俊; 黄欢; 钟强; 陈志新 (Kongzhi Yu Xinxi Jishu)
Neutral point drifting technology based on the same harmonic distribution of line voltage is proposed. With the optimization of carrier phase-shifted angle and frequency modulation ratio, the harmonic distribution of three line voltages can be consistent. Comparing with the normal failure power unit treatment, the amplitude of output voltage can be increased and THD (Total Harmonic Distortion) can be decreased. Simulation results verify the validity of the proposed method.